ANALISIS PENGARUH INFLASI, NILAI TUKAR RUPIAH DAN PRODUK DOMESTIK BRUTO (PDRB) TERHADAP FOREIGN DIRECT INVESTMENT DI PROVINSI RIAU TAHUN 2000-2020 - Agustina Titin; Aulia Fahda Ando; Richard Rahmat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of Inflation Rate, Exchange Rate and Gross Regional Domestic Product (GDP) on Foreign Direct Investment in Riau Province in 2000-2020. This study uses secondary data obtained from activity report data and published statistical data, namely the official website of the Central Statistics Agency, the Investment Activity Institute and the One Stop Integrated Investment and Investment Service (DPMPTSP). In this study using the Ordinary Least Square (OLS) method multiple linear regression technique with eviews 10 program. The results show that the Exchange Rate has a positive and significant effect on Foreign Direct Investment (FDI) with a significant level of 5% obtained from the probability value of F Statistics < (0.05) which is 0.0024 < (0.05). Partially the level of inflation and GDP has a positive but not significant effect on foreign investment entering Riau Province. The ability of the three independent variables to explain the dependent variable with an adjusted Rsquare value of 0.684671. This means that the contribution of the influence of the two independent variables the dependent variable is 68.46% while the remaining 31.54% is influenced by other factors outside of this study such as the existence of government policy regulations in regulating the entry of investment into a country and region.Keywords : FDI, Inflation, Exchange Rate, and Gross Regional Domestic Product